ADVERSITY QUOTIENT AND SELF-REGULATED LEARNING AMONG ORPHANED AND UNDERPRIVILEGED STUDENTS IN ISLAMIC BOARDING SCHOOLS - Cahyo Wulandari, Desi Fitri; Hardew, Ayatullah Kutub (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Orphaned and underprivileged students face significant challenges, such as life pressures, dual responsibilities, lack of study strategies, low motivation, dependence on guidance, and difficulty managing time, thus requiring self-regulated learning and adversity quotient. This study aims to determine the correlation between Adversity Quotient and Self-Regulated Learning among orphans and underprivileged students at the Islamic boarding school. The research sample consists of 275 students from the Orphaned and Underprivileged Islamic Boarding School using the Criterion Sampling technique. This study uses a likert scale with a reliability coefficient > 0.70. Data analysis was conducted using Pearson's product-moment correlation analysis. In the research results, an effective contribution of 32.7% from adversity quotient was obtained, indicating a significant positive relationship between adversity quotient and self-regulated learning among students at the Orphanage and Underprivileged Islamic Boarding School. This finding emphasizes the importance of developing adversity quotient to enhance the self-regulated learning of students in facing various challenges